Sistem Informasi Pengelolaan Hutang Piutang Di Toko Bangunan Putri Ayu Bawen - Heribertus Ary Setyadi (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
ABSTRACT - The increasing construction of houses, flats and apartments have a positive impact for building materials business. Building materials stores have become major suppliers in the current business property stretch. Putri Ayu is a building materials store that sells various types of building materials such as cement, wood, ceramaic, wood, iron, paint, mild steel, home appliances and other types. The system of purchase and sale is done by cash and non cash or termin as agreed. Sales transactions and inventory information as well as debt management are the main issues. The purpose of this study is to produce a system that can help process transactions in the building of Putri Ayu Bawen including the management of accounts payable and can provide information or reports or recapitulation required. System analysis used in this research started from the analysis of running system, system weakness analysis using PIECES method and information requirement analysis. In the system design created context diagram, Data Flow Diagram, input design, output design and database design. The system generated in this study was made using Visual Basic programming and Ms.Access as its data base. The developing system can process data categories, goods, suppliers and customers. Transactions contained in the system include purchase, sale, payment of debt to the supplier and payment of customer debt. The system can also print sales report, delivery orders letters and some lists, reports and recapitulation required by the owner.Keywords : Debt, Receivable, Building Material Shop, Visual Basic